Influence of exercise intensity in older persons with unchanged habitual nutritional intake: skeletal muscle and endocrine adaptations - Onambélé-Pearson, Gladys Leopoldine (Springer Netherlands, 2010)
Long-term adherence to training programmes is difficult to attain. Yet, the benefits of exercise to general health and well-being are undeniable. Any measure to demonstrate the minimum required exercise for maximal benefit to a person is a promising avenue towards increasing the uptake and adherence to physical activity for the general public. The purpose of this study was to compare the effects of two different intensities of resistance training in healthy older adults. We hypothesised that compared to high-intensity resistance exercise, relatively low training intensity could also improve in vivo markers of healthy physiologic and endocrine functions in previously sedentary older individuals. Thirty (out of a possible 34 recruited) older adults were randomly assigned to low (LowR, i.e. ∼40% one repetition maximum (1RM)) versus high-resistance training (HighR, i.e. ∼80% 1RM) for 12 weeks. Neither intervention significantly impacted upon body composition markers including: body mass index (BMI), waist/hip ratio and bioelectric impedance. Muscle strength data showed an advantage for the HighR protocol with 51 ± 4% and 22.4 ± 10.2% (P < 0.05) improvements in 1RM strength and bilateral knee extension torque, respectively, compared with 17 ± 1% and 10.3 ± 4.7% (P < 0.05) increments in 1RM strength and bilateral torque in the LowR group. Unilateral torque did not change significantly in either group. Quadriceps muscle thickness data also showed a significantly greater benefit of the HighR protocol (5.8 ± 2.6% increase) compared with the LowR protocol (no change). Functional ability tests, including Get-up-and-go (GUG), Standing from lying and the 6-min walk, showed changes of −11.6 ± 4.8%, −15.6% and 8.5 ± 1.7% (P < 0.05), respectively, in HighR compared with only one significant improvement in the LowR, namely a −10.8 ± 3% (P < 0.05) improvement in the GUG test. Overnight fasting serum levels of IGFBP-3 increased, NPY decreased and TNF-α decreased significantly in the LowR group. Serum levels of glucose increased and NPY decreased significantly in HighR. Circulating levels of I, IL-6 and IGF-1 did not change with either intervention. In vivo physiologic changes show functional advantages for older persons carrying out high-resistance training. At the endocrine level, such an advantage is not clear. In fact, in terms of changes in sera levels of fasting glucose, IGFBP-3 and TNF-α, there appears to be an advantage to carrying out the lower intensity exercises for the aged populations where endocrine adaptations are key.